Penerapan Terapi Dzikir Untuk Menurunkan Tekanan Darah Pada Pasien Stroke Akut Di HCU Neuro Anggrek 2 RSUD Dr. Moewardi Surakarta - Faridha Sholikhah Ahyari; Fida’ Husain; Isti Haniyatun Khasanah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Background:Nearly 70-94% of acute stroke patients experience increased blood pressure (hypertension). Hypertension is the main triggering factor for the occurrence of strokes, both hemorrhagic and ischemic strokes, one way is to provide non-pharmacological therapy with dhikr relaxation (remembrance of Allah). Objective: to find out the application of dhikr therapy to reduce blood pressure in acute stroke patients at HCU Neuro Anggrek 2 RSUD Dr. Moewardi Surakarta. Method: the application of this journal uses a descriptive method with a case study approach to 2 respondents according to the inclusion and exclusion criteria, the independent variable of the research is dhikr therapy, namely therapy that is carried out by reminding respondents to Allah SWT through recordings of reading recitation sentences, by adjusting the position of the respondent first first, namely supine position with head elevation of 30o, then listen to the recorded dhikr sentences using hands-free to the respondent 3 times a day for 10 minutes for 3 days. Results: Based on the results of the application that has been carried out, there is a decrease in blood pressure before and after the dhikr relaxation therapy is performed. Conclusion: There is a decrease in blood pressure before and after the application of dhikr from first degree hypertension to prehypertension.